2016
DOI: 10.3390/cryst6110140
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis, Characterization, and Visible-light Photocatalytic Activities of 3D Hierarchical Bi2S3 Architectures Assembled by Nanoplatelets

Abstract: 3D hierarchical Bi 2 S 3 architectures have been successfully synthesized via a simple and effective hydrothermal process. The as-prepared Bi 2 S 3 samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), nitrogen adsorption-desorption isotherms, and UV-vis diffuse reflectance spectrum (DRS). The observation of field emission scanning electron microscope (FESEM) images showed that numerous nanoplatelets are randomly arranged and intercon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…As reported in the previous work [32,60,61], 60 mL MB aqueous solution (1.0 × 10 −5 M) was added into a culture dish with a diameter of 70 mm which was coated with 80 mg prepared catalyst on the surface. Two daylight lamps (60 W, λ ≥ 400 nm) were used as a light source to trigger the photocatalytic reaction.…”
Section: Photocatalytic Experimentsmentioning
confidence: 99%
“…As reported in the previous work [32,60,61], 60 mL MB aqueous solution (1.0 × 10 −5 M) was added into a culture dish with a diameter of 70 mm which was coated with 80 mg prepared catalyst on the surface. Two daylight lamps (60 W, λ ≥ 400 nm) were used as a light source to trigger the photocatalytic reaction.…”
Section: Photocatalytic Experimentsmentioning
confidence: 99%
“…14 Photodegradation of methylene blue in the presence of Cu 0.4 Zn 0.6 Fe 2 O 4 /TiO 2 -Bi 2 S 3 nanostructures is unlikely a dye-sensitized reaction. This proposition stems from the facts that methylene blue degradation on Bi 2 S 3 is a photocatalyzed one 33 and methyl orange 33 and rhodamine B 10,11 dyes are also photocatalytically degraded by Bi 2 S 3 . Furthermore, Bi 2 S 3 -deposited TiO 2 photocatalyzes degradation of methyl orange, 16,18 orange G, 14 orange II, 15 4-hydroxybenzoic acid, 15 and 2,4-dichlorophenoxyacetic acid 17 under visible light.…”
Section: Resultsmentioning
confidence: 99%
“…10 4 –10 5 cm –1 ) and reasonable incident photon to electron conversion efficiency . Visible light photocatalytic mineralization of organic pollutants by nanostructured Bi 2 S 3 is well established. , TiO 2 could be sensitized and enabled to absorb light of longer wavelength, by coupling with a narrow-band-gap semiconductor such as Bi 2 S 3 . Bi 2 S 3 /TiO 2 heterojunction enhances charge separation, and nanocrystalline Bi 2 S 3 /TiO 2 shows improved photocurrent ( J ) with visible light .…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [22] used a lowtemperature molten-salt method for the preparation of rod-like Bi2S3 single crystals and investigated the effects of annealing temperature and the dosage of molten salt (KSCN) on the morphology and Hg 0 elimination properties of Bi2S3, which showed that Bi2S3 single crystals have a better Hg 0 capture ability due to the one-dimensional rod-like structure with sufficient exposed adsorption sites, as well as the higher binding energy of Bi 3+ species. Jia et al [23] utilized a CTAB-assisted hydrothermal synthesis route to obtain 3D Bi2S3 for photocatalytic degradation of RhB. However, for the above-mentioned methods for synthesizing Bi2S3, complex and expensive equipment is generally required, or additional surfactants, ligands, or toxic organic solvents are needed [20][21][22][23][24][25][26], which are not environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Jia et al [23] utilized a CTAB-assisted hydrothermal synthesis route to obtain 3D Bi2S3 for photocatalytic degradation of RhB. However, for the above-mentioned methods for synthesizing Bi2S3, complex and expensive equipment is generally required, or additional surfactants, ligands, or toxic organic solvents are needed [20][21][22][23][24][25][26], which are not environmentally friendly. Furthermore, most studies have focused on a single morphology of Bi2S3, and the research on the 1D/2D Bi2S3 is relatively limited, indicating the need for further exploration.…”
Section: Introductionmentioning
confidence: 99%